(untitled) (CIPEEX, 2025)
Regenerative medicine has emerged as an innovative and promising field for tissue repair, particularly in addressing the challenges posed by complex wounds, which often exhibit impaired healing capacity, high susceptibility to infection, and a significant impact on patients’ quality of life. In this context, the use of biomaterials combined with natural bioactive compounds represents a strategy capable of enhancing tissue regeneration by integrating the structural properties of the extracellular matrix (ECM) with the biological activity of natural substances. This study aimed to develop and evaluate decellularized porcine skin scaffolds functionalized with phenolic extracts and honey, exploring their applicability as a therapeutic alternative for the treatment of complex wounds. The decellularization process was performed through sequential washes with PBS, SDS, and Triton X-100. This protocol proved effective in removing cellular components while preserving ECM organization, a critical feature for maintaining the tridimensional architecture that supports cellular growth. Preservation of these structural characteristics was confirmed by histological analyses and scanning electron microscopy, which revealed well-organized collagen fibers and absence of cellular residues. Scaffold biocompatibility was assessed through in vitro assays, which demonstrated their ability to provide a favorable microenvironment for cell adhesion, proliferation, and viability, highlighting their potential for clinical applications. Subsequently, in vivo experiments were performed using a Wistar rat model, with animals allocated into three experimental groups: conventional suture (control), non-functionalized scaffold, and bioactive-functionalized scaffold. The results showed that animals treated with bioactive scaffolds exhibited approximately 30% faster wound closure compared to controls, along with a 50% reduction in inflammatory markers. Moreover, improved organization of type I and III collagen fibers, absence of infection, and more efficient epidermal regeneration were observed, resulting in a 40% reduction in fibrosis formation compared with the other groups. These findings underscore the relevance of combining preserved ECM architecture with the antioxidant, antimicrobial, and anti-inflammatory effects of natural compounds. In conclusion, the integration of acellular porcine-derived scaffolds with natural bioactive compounds represents an innovative, safe, and effective therapeutic strategy to accelerate wound healing and promote high-quality tissue regeneration. The results demonstrate not only the feasibility of this approach but also its translational potential, paving the way for the development of personalized therapies in the management of complex wounds. Thus, this study contributes to the advancement of regenerative medicine by supporting the design of novel biomaterials that combine sustainability, low cost, and high clinical efficacy. Keywords: Biomaterials; Regenerative medicine; Scaffold.